Investigations of Processing–Induced Structural Changes in Horse Type-I Collagen at Sub and Supramolecular Levels - Terzi, Alberta; Gallo, Nunzia; Bettini, Simona; Sibillano, Teresa; Altamura, Davide; Campa, Lorena; Natali, Maria Lucia; Salvatore, Luca; Madaghiele, Marta; De Caro, Liberato; Valli, Ludovico; Sannino, Alessandro; et al. (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this work was to evaluate the effects of different extraction and material processing protocols on the collagen structure and hierarchical organization of equine tendons . Wide and Small Angle X ray Scattering investigations on raw powders and thin films revealed that not only the extraction and purification treatments, but also the processing conditions may affect the extent of the protein crystalline domain and induce a nanoscale “shield effect”. This is due to the supramolecular fiber organization, which protects the atomic scale structure from the modifications occurring during fabrication protocols. Moreover, X rays analyses and Fourier Transform Infrared spectroscopy performed on the biomaterial shed light on the relation between processing conditions, triple helical content and organization in atomic and nanoscale domains. It was found that the mechanical homogenization of the slurry in acidic solution was the treatment ensuring a high content of super-organization of collagen into triple helices and a lower crystalline domain in the material. Finally, mechanical tensile tests were realized and proved that the acidic solution was the condition which most enhanced both mechanical stiffness and supramolecular fiber organization of the films.